Testing a multi-behavioral intervention to improve oral health behaviors in the pediatric dental surgery population: protocol for the PROTECT trial - Buscemi, Joanna; Borowski, Teresa G.; Avenetti, David; Tussing-Humphreys, Lisa; Martin, Molly; Atkins, Marc S.; Marshall, Teresa; Berbaum, Michael; Lee, Helen H. (Frontiers in Public Health, 2025)
Severe early childhood caries (S-ECC) is a common disease within marginalized pediatric populations. S-ECC is often treated under general anesthesia to facilitate extensive treatment in young children, but treatment does not address etiology of an infectious disease that is rooted in health behaviors. Without behavior changes related to toothbrushing and sugar consumption, many children experience recurrent disease, and some require subsequent surgeries. To improve post-surgery oral health, we developed PROTECT (Preventing Recurrent Operations Targeting Early Childhood Caries Treatment), a community health worker (CHW)-delivered behavioral intervention for caregivers that focuses on children’s oral health behaviors. This study aims to test the efficacy of the PROTECT intervention compared to Usual Care (UC), to improve behavioral oral health outcomes. We will conduct a randomized clinical trial to test the efficacy of PROTECT (n = 210) compared to UC (n = 210) in the pediatric DGA (dental surgery under general anesthesia) population. We developed PROTECT through an iterative process, incorporating feedback from caregivers, dentists, and community health workers and through a small pilot trial. Caregivers will be recruited at their dental clinic and then will engage in a 10-session intervention with a community health worker. Topics covered will include education about toothbrushing and sugar consumption, behavioral strategies (e.g., goal setting, problem solving, self-monitoring), positive parenting and stress management and maintenance. Our two primary outcomes are parental assisted toothbrushing (twice/day, 2 min each time) and reduced added sugar consumption (less than 10% of overall daily caloric intake). Proposed mechanisms of change are self-efficacy and positive parenting. The ultimate goal of PROTECT is to prevent subsequent surgical events for children presenting with S-ECC to prevent further chronic disease and reduce costs and stress for families who already experience high levels of systemic barriers to their health.